قرآن میں مذکور رنگوں کی تعبیر اور ان کے انسانی نفسیات پر اثرات: The Interpretation of Colors in the Qur’an and Their Impact on Human Psychology - Shazia, Dr.; Mumtaz, Laiba (Al-Amīr Research Journal for Islamic Studies, 2024)
The Qur’an, as a divine revelation, employs a rich symbolic language to convey deep spiritual and psychological messages. Among its many symbols, colors hold significant importance, reflecting divine wisdom, human emotions, and natural phenomena. This study explores the Quranic references to colors such as green, white, black, yellow, blue, and red, analyzing their spiritual meanings and psychological impacts on human behavior. Green, symbolizing paradise, represents tranquility, hope, and renewal, promoting mental peace. White signifies purity, righteousness, and clarity, fostering moral integrity. Black, often associated with adversity, serves as a reminder of the transient nature of trials, while yellow has dual connotations—energy and caution. Red and blue, carrying diverse meanings, signify passion, power, sacrifice, and depth. The psychological influence of these colors extends beyond spiritual significance, affecting human mood, decision-making, and cognitive responses. By integrating Quranic interpretations with modern psychological insights, this study highlights how divine symbolism in colors enhances emotional well-being and ethical awareness. Keywords: Qur’anic colors, symbolism, spirituality, psychology, human emotions, divine wisdom, behavioral influence